Enhanced Energetic Neutral Atom Imaging - Scime, Earl E.; Keesee, Amy M. (Frontiers in Astronomy and Space Sciences, 2019)
Over the past two decades, instruments designed to image plasmas in energetic neutral atom (ENA) emission have flown in space. In contrast to typical satellite-based in situ instruments, ENA imagers provide a global view of the magnetosphere because they remotely measure ion distributions via neutrals that are not tied to the magnetic field. An intrinsic challenge that arises during analysis of magnetospheric ENA images is that the ENA fluxes are integrated along the line-of-sight of the instrument. We propose a method of enhancing ENA emission from a localized region in space, thereby enabling spatially resolved measurements of ENA emission in a remotely obtained ENA image. Here we show that releases of modest volumes (~ 1.4 m3) of liquid hydrogen in space are sufficient to accomplish the ENA localization.